Development Of Bilingual Getrans Teaching Aids To Understand Geometry Transformation Material - Utami, Rini; Hidayah, Nurina; Sidqi, Muhammad Fajru; Kuncoro, Sigit (Universitas Wiralodra, 2024)
This research aims to develop bilingual getrans teaching aids that can be used to visualise the concept of geometry transformation. The urgency of this research lies in the effort to facilitate students' understanding of abstract concepts in geometric transformations where the development of getrans teaching aids allows students to learn actively, involving physical and visual, which is believed to improve understanding and retention of concepts. Utilizing the 4D model, the Research and Development (R&D) approach is applied. The four phases of the 4D development model are defined, designed, developed, and disseminated. The findings showed that students had trouble grasping the idea of geometric transformation at the define stage. At the design stage, preparation for the development of bilingual getrans teaching aids was carried out. At the development stage, getrans props were made as well as validation of video results by experts and limited trials to students. Then at the dissemination stage, the revised video results were disseminated based on expert advice. The conclusion of this research is that bilingual getrans teaching aids can be used for learning mathematics which students can better understand changes in position, rotation, reflection, or dilation of objects in geometry with better.